2009
DOI: 10.1007/s10238-009-0042-4
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-2 in CD8+ T cells correlates with Banff score during organ rejection in liver transplant recipients

Abstract: The aim of this study is to compare the histological grading of acute organ rejection according to the Banff score with intracellular interleukin-2 (IL-2) concentrations in cytotoxic CD8+ T cells from peripheral blood samples. 66 recipients after liver transplantation and 20 healthy controls were included into this study. Blood samples of liver transplant recipients were collected beside routine visits or, in case of suspected organ rejection, with additional liver biopsy. For cytometry, the blood cells were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 19 publications
2
7
0
1
Order By: Relevance
“…The authors found that intracellular IL-2 expression in CD8 + T cells before transplantation was closely related to the onset of AR. These results strongly correlate with those observed by Akoglu et al (2009), who found that IL-2 expression in CD8 + T cells correlated with Banff score during organ rejection in adult liver transplant recipients. In a study of immunosuppression drug weaning in stable long-term liver transplant recipients, Millán et al showed that soluble IFN-γ and intracellular IFN-γ and IL-2 were significantly increased in patients who rejected, suggesting that these biomarkers may prove useful to identify patients at high risk of AR (Millán et al 2010).…”
Section: Intracellular Cytokine Staining (Ics)supporting
confidence: 93%
“…The authors found that intracellular IL-2 expression in CD8 + T cells before transplantation was closely related to the onset of AR. These results strongly correlate with those observed by Akoglu et al (2009), who found that IL-2 expression in CD8 + T cells correlated with Banff score during organ rejection in adult liver transplant recipients. In a study of immunosuppression drug weaning in stable long-term liver transplant recipients, Millán et al showed that soluble IFN-γ and intracellular IFN-γ and IL-2 were significantly increased in patients who rejected, suggesting that these biomarkers may prove useful to identify patients at high risk of AR (Millán et al 2010).…”
Section: Intracellular Cytokine Staining (Ics)supporting
confidence: 93%
“…The percentage of CD8 cells producing IL-2 was increased in patients with rejection after a liver transplant already before the transplantation [96] , indicating activation of the immune system. These results were confirmed in two studies [64,97] . The measurement of IL-2-producing T-cells is relatively easy and reproducible by means of flow cytometry, which is why this biomarker seems suitable for use in clinical trials with calcineurin inhibitors, which, however, have not been conducted yet.…”
Section: Interleukin-2 In Cd8 T-cellssupporting
confidence: 65%
“…The results from Boleslaswki et al were confirmed in two recent studies. Akoglu and coworkers demonstrated an association between IL-2-producing CD8 þ T cells and the histological Banff score in 66 patients after liver transplantation [22]. Furthermore, Millán et al, who investigated the numbers of IL-2-producing CD8 þ T cells in stable liver transplant recipients undergoing weaning of immunosuppressive therapy during the withdrawal protocol, found that the percentage of IL-2-producing CD8 þ T cells was significantly higher in patients who rejected, compared to those who did not reject [25].…”
Section: Interleukin-2 In Cd8 D T Cellsmentioning
confidence: 97%
“…The intraand inter-assay imprecision of this procedure appears to be acceptable (CV < 15% as stated by different authors [20,21]). However, as in other flow cytometric assays, standardization remains a critical issue since, for example, different conditions for mitogenic stimulation lead to a high inter-laboratory variation [22].…”
Section: Interleukin-2 In Cd8 D T Cellsmentioning
confidence: 99%